2022
DOI: 10.1200/op.21.00357
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Strategies for Robust Survivorship Program Implementation: A Qualitative Analysis of Cancer Programs

Abstract: PURPOSE The Commission on Cancer seeks to promote robust survivorship programs among accredited cancer programs. In practice, cancer programs' survivorship programs range from cursory (eg, developing care plans without robust services) to robust (eg, facilitating follow-up care). To inform cancer programs' future efforts, in this study, we identified the implementation strategies that cancer programs used to achieve robust survivorship programs, distinguishing them from cursory programs. METHODS We sampled 39 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This is not surprising since previous literature has demonstrated that even robust survivorship programs face challenges and implementation struggles. 35 Actions that can be implemented to help overcome these challenges include educational activities for increasing physician awareness, inclusion of digital solutions for minimizing time and distance-related burden (eg, virtual Transition Day), formal economic valorization with protected time for pathway delivery, and continuous cocreation of pathway components with patients to ensure the that they respond to their needs. Moreover, an upfront identification of patients with very low clinical complexity and high self-management skills and who do not need extensive pathway resources is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising since previous literature has demonstrated that even robust survivorship programs face challenges and implementation struggles. 35 Actions that can be implemented to help overcome these challenges include educational activities for increasing physician awareness, inclusion of digital solutions for minimizing time and distance-related burden (eg, virtual Transition Day), formal economic valorization with protected time for pathway delivery, and continuous cocreation of pathway components with patients to ensure the that they respond to their needs. Moreover, an upfront identification of patients with very low clinical complexity and high self-management skills and who do not need extensive pathway resources is desirable.…”
Section: Discussionmentioning
confidence: 99%